L’influence perçue des instruments d’action publique fédéraux et provinciaux sur la production de recherche universitaire au Canada - Bégin-Caouette, Olivier; Nakano Koga, Silvia Mirlene; Karram Stephenson, Grace (Canadian Journal of Higher Education, 2020)
This article compares how faculty members from British Columbia, Ontario and Quebec perceive the influence of federal and provincial policy instruments on the level of academic research production in their province. Mean scores, and a MANOVAfollowed by Dunnett C post-hoc tests based on a questionnaire completed by 786 participants reveal that professors perceived federal instruments as being more influential than provincial instruments, but also that there is a significant difference in the average score given by Quebec professors to provincial instruments, when compared to their counterparts in the other provinces.